Good Governance in LAZISNU (Perspective Islamic Accounting and Donation Based Crowdfunding) - Novendi Arkham Mubtadi (Journal of Nahdlatul Ulama Studies, 2025)
Governance in zakat management organizations (OPZ) is a crucial issue because ZIS funds (zakat, infaq, and sadaqah) constitute a public trust (amanah) that requires transparency, accountability, and sharia compliance. At the same time, the expansion of digital channels through donation-based crowdfunding creates opportunities to broaden fundraising, yet it also demands robust digital governance standards to build donor trust. This study aims to analyze LAZISNU’s good governance from the perspective of Islamic Accounting through Sharia Enterprise Theory (SET) and to assess the effectiveness of donation-based crowdfunding governance on LAZISNU’s online platform. The study employs a qualitative method using a literature review and program document analysis with two approaches: (1) mapping LAZISNU’s programs into the three SET dimensions contribution to Allah (education and health), contribution to humans (economic empowerment), and contribution to nature (disaster relief) as a basis for moral-spiritual and social accountability; and (2) evaluating crowdfunding effectiveness by comparing platform donation achievements against program targets and information disclosure indicators. The findings show that LAZISNU’s program implementation and ZIS fund management tend to align with SET because the program portfolio represents worship, social, environmental dimensions. However, donation-based crowdfunding governance is assessed as not yet effective, as reflected in low online donation achievements relative to targets during the evaluation period, indicating weak trust-building mechanisms through progress updates, impact evidence, and adequate disclosure. This study recommends strengthening digital governance through integrated reporting (audited financial reporting, program output–outcome reporting, and sharia compliance reporting), regular and transparent platform updates, clearer fund utilization flows, and volunteer/community mobilization strategies to expand campaign reach. These findings provide a reference for policymakers and OPZ managers in improving good governance systems and enhancing the effectiveness of digital-based fundraising.